Functional Mechanism of the Efflux Pumps Transcription Regulators From Pseudomonas aeruginosa Based on 3D Structures - Housseini B Issa, Karim; Phan, Gilles; Broutin, Isabelle (Frontiers in Molecular Biosciences, 2018)
Bacterial antibiotic resistance is a worldwide health problem that deserves important research attention in order to develop new therapeutic strategies. Recently, the World Health Organization (WHO) classified Pseudomonas aeruginosa as one of the priority bacteria for which new antibiotics are urgently needed. In this opportunistic pathogen, antibiotics efflux is one of the most prevalent mechanisms where the drug is efficiently expulsed through the cell-wall. This resistance mechanism is highly correlated to the expression level of efflux pumps of the resistance-nodulation-cell division (RND) family, which is finely tuned by gene regulators. Thus, it is worthwhile considering the efflux pump regulators of P. aeruginosa as promising therapeutical targets alternative. Several families of regulators have been identified, including activators and repressors that control the genetic expression of the pumps in response to an extracellular signal, such as the presence of the antibiotic or other environmental modifications. In this review, based on different crystallographic structures solved from archetypal bacteria, we will first focus on the molecular mechanism of the regulator families involved in the RND efflux pump expression in P. aeruginosa, which are TetR, LysR, MarR, AraC and the two-components system (TCS). Finally, the regulators of known structure from P. aeruginosa will be presented.